2021
DOI: 10.1111/pops.12746
|View full text |Cite
|
Sign up to set email alerts
|

Australasian Public Awareness and Belief in Conspiracy Theories: Motivational Correlates

Abstract: Conspiracism is not restricted to the fringe dwellers of society. International research suggests that such beliefs are quite common and that conspiracy theories may serve three basic psychological motives (i.e., epistemic, existential, and relational) for individuals. Yet, little is known about conspiracy theory awareness or conspiracism in Australasia. We report the first large systematic investigation of system justifying motives using two nationally representative samples of Australians (n = 1,011) and New… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 61 publications
2
17
0
1
Order By: Relevance
“…For example, Newheiser et al (2011) showed that the more strongly someone endorsed New Age beliefs, the more likely they believed the Da Vinci Code conspiracy. Similarly, Marques et al (2021) found a positive relationship between a one‐item measure that combined religion and spirituality (i.e., religion/spirituality) and belief in local and international conspiracy theories. However, both these studies had limited operationalizations of either conspiracy beliefs or spirituality—while the former investigated relation with one specific conspiracy theory, the latter combined religion and spirituality in one item.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, Newheiser et al (2011) showed that the more strongly someone endorsed New Age beliefs, the more likely they believed the Da Vinci Code conspiracy. Similarly, Marques et al (2021) found a positive relationship between a one‐item measure that combined religion and spirituality (i.e., religion/spirituality) and belief in local and international conspiracy theories. However, both these studies had limited operationalizations of either conspiracy beliefs or spirituality—while the former investigated relation with one specific conspiracy theory, the latter combined religion and spirituality in one item.…”
Section: Introductionmentioning
confidence: 90%
“…However, there is still little empirical groundwork in understanding how these variables work together and which ones are more relevant. Only rarely have studies made strides to assess the joint contribution of various predictors (e.g., Marques et al, 2021). This is problematic, especially because many psychological motives or concepts overlap (Douglas et al, 2017), so exploring individual correlates might fail to assess the relative importance of predictors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Newheiser et al (2011) showed that the more strongly someone endorsed New Age beliefs, the more likely they believed the Da Vinci Code conspiracy. Similarly, Marques et al (2021) found a positive relationship between a one-item measure that combined religion and spirituality (i.e., religion/spirituality) and belief in local and international conspiracy theories. However, both these studies had limited operationalizations of either conspiracy beliefs or spirituality-while the former investigated relation with one specific conspiracy theory, the latter combined religion and spirituality in one item.…”
Section: Spiritualitymentioning
confidence: 85%
“…However, there is still little empirical groundwork in understanding how these variables work together and which ones are more relevant. Only rarely have studies made strides to assess the joint contribution of various predictors (e.g., Marques et al, 2021). This is problematic, especially because many psychological motives or concepts overlap (Douglas et al, 2017), so exploring individual correlates might fail to assess the relative importance of predictors.…”
Section: The Aims Of the Present Studymentioning
confidence: 99%
“…For example, a nationally representative sample of 1935 members of the American public (Oliver & Wood, 2014) found that 55% of participants expressed agreement with at least one of seven conspiracy theories including narratives claiming that vapour trails left by aircraft are actually chemical agents ("chemtrails") sprayed as part of a clandestine government programme (9% agreed). A more recent study of conspiracy beliefs in demographically representative samples of Australians and New Zealanders reported that approximately half of the participants from each nation (56.7% Australians and 50.1% of New Zealanders) endorsed one or more of seven local conspiracy theories (Marques et al, 2021). Furthermore, these data showed that some people believed in several conspiracy theories, whereas others believed in none.…”
Section: Introductionmentioning
confidence: 96%